Enhancing the Mechanical Properties of Biodegradable Mg Alloys Processed by Warm HPT and Thermal Treatments - Andrea Mizelli-Ojdanic (MDPI AG, 2021)
In this study, several biodegradable Mg alloys (Mg5Zn, Mg5Zn0.3Ca, Mg5Zn0.15Ca, and Mg5Zn0.15Ca0.15Zr, numbers in wt%) were investigated after thermomechanical processing via high-pressure torsion (HPT) at elevated temperature as well as after additional heat treatments. Indirect and direct analyses of microstructure revealed that the significant strength increases arise not only from dislocations and precipitates but also from vacancy agglomerates. By contrast with former low-temperature processing routes applied by the authors, a significant ductility was obtained because of temperature-induced dynamic recovery. The low initial values of Young’s modulus were not significantly affected by warm HPT-processing. nor by heat treatments afterwards. Also, corrosion resistance did not change or even increase during those treatments. Altogether, the study reveals a viable processing route for the optimization of Mg alloys to provide enhanced mechanical properties while leaving the corrosion properties unaffected, suggesting it for the use as biodegradable implant material.